Age Trajectories of O2 Saturation and Levels of Serum Bicarbonate or End-Tidal CO2 Across the Life Course of Women and Men: Insights from EHR and PSG Data - Leping Li; Min Shi; David M. Umbach; Zheng Fan (Biomolecules)
To elucidate the changes in gas exchange across the life course, we estimated the age trajectories of O2 saturation, CO2 (as either end-tidal or serum bicarbonate), resting heart rate, and resting respiratory rate from age 2 yr onward in female and male patients separately. We utilized two sources’ data: electronic health records (EHR) representing ambulatory visits of approximately 53,000 individuals and sleep clinic polysomnogram (PSG) records representing an additional ~21,000. We used linear regression to estimate age-group-specific mean response levels for women and men. We compared estimated female–male differences between pre- and post-pubertal children and between pre- and post-menopausal periods among adults. Women between 15 and 45 years had higher O2 saturation and lower serum bicarbonate levels or end-tidal CO2 levels than men of similar ages. For O2 saturation and for both measures of CO2, the female–male difference was larger on average among adults at pre-menopausal ages than those at post-menopausal ages. Women had higher O2 saturation throughout their lives than men; however, the difference disappeared in the elderly. Women between menarche and menopause had significantly lower end-tidal CO2 and serum bicarbonate than men of similar ages. After menopause, however, women appeared to have higher mean levels of both end-tidal CO2 and serum bicarbonate than men.